2007
DOI: 10.1152/ajpendo.00271.2007
|View full text |Cite
|
Sign up to set email alerts
|

Akt activation and augmented fibronectin production in hyperhexosemia

Abstract: Dysmetabolic state in diabetes may lead to augmented synthesis of extracellular matrix (ECM) proteins. In the endothelial cells, we have previously demonstrated that glucose-induced fibronectin (FN) production and that of its splice variant, EDB+FN, is regulated by protein kinase B (PKB, also known as Akt). In this study, we investigated the role of Akt1 in ECM protein production in the organs affected by chronic diabetic complications. We studied Akt1/PKBα knockout mice and wild-type control littermates. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…We have previously demonstrated that, in endothelial cells, hyperglycemia-induced protein kinase C and mitogen-activated protein kinase, as well as protein kinase B activation, may enhance the activity of p300 (30). All such pathways have been demonstrated in the heart of diabetic animals and may potentially contribute to p300 activation (12,23,49). This study supports the notion that p300 may represent a common final pathway upon which several signaling mechanisms may converge.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously demonstrated that, in endothelial cells, hyperglycemia-induced protein kinase C and mitogen-activated protein kinase, as well as protein kinase B activation, may enhance the activity of p300 (30). All such pathways have been demonstrated in the heart of diabetic animals and may potentially contribute to p300 activation (12,23,49). This study supports the notion that p300 may represent a common final pathway upon which several signaling mechanisms may converge.…”
Section: Discussionsupporting
confidence: 83%
“…Mice kidneys: Proteins were extracted from frozen mouse kidneys using RIPA [43] For microscopy, kidneys were fixed in 4% formaldehyde. Paraffin-embedded kidney sections were dewaxed, rehydrated and stained.…”
Section: Methodsmentioning
confidence: 99%
“…These contrasting findings highlight the complex nature of miRNA research. Other miRNA that have been implicated in contributing to fibrogenesis in DN are miR-216a and miR-217 (Kato et al 2009;Xin et al 2007), miR-377 that regulates fibronectin expression (Wang et al 2008) and studies have shown TGF-β1-induced EMT is associated with upregulation of miR-21 (Zavadil et al 2007;Lan et al unpublished data). We have recently observed that miR-21 expression was significantly upregulated in a mouse model of obstructive nephropathy and was also upregulated by TGF-β/Smad3 signalling pathway.…”
Section: Mirna and Type II Emtmentioning
confidence: 99%